IMPROVING THE TOOLS OF STATE MANAGEMENT OF LOCAL ECONOMIC DEVELOPMENT - PRIAMUKHINA, Natalia; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study emphasizes the urgency of the problem of improving the system of tools that can be effectively used to ensure effective and balanced local socio-economic development in Ukraine.The purpose of the study is to improve the tools of state management of local economic development.It has been proven that the effective regulation of the development of territorial communities is based on the capacity of the tools of local economic development, which is a complete complex consisting of goals, strategic tasks, goals, mechanisms and means of regulation. The goal of designing local economic development is determined, namely, in the form of developing tools and means of increasing the resource potential of strengthening the capacity of the community through: improving the investment climate and activating the business environment; improvement of entrepreneurial skills of the local population; strengthening the budgetary stability of the community as the basis of economic progress; strengthening cooperation with various target groups (youth, women, IDPs).It has been proven that in the process of ensuring the local economic development of the community, it is important to focus on solving the following tasks: development of tools for strengthening the economic capacity (self-sufficiency) of the community; improvement of resources attraction tools; strengthening of budget sustainability; development of means and measures for activation of entrepreneurial activity; development of tools for youth participation in decision-making and implementation of ideas for the future vision of community development. It is summarized that the implementation of the local economic development program involves the interaction of such subjects as: state and local self-government bodies, industry associations and business associations, business entities, public organizations and political parties, and the population. The key elements of the implementation mechanism of the local economic development program have been identified.
Keywords: local economic development; governance; Local Government; territorial communities; policy tools